Being in a process of transition to psychosis, as narrated by adults with psychotic illnesses acutely admitted to hospital - Sebergsen, K (J Psychiatr Ment Health Nurs, 2014)
ACCESSIBLE SUMMARY: Early intervention to prevent and reduce new episodes of psychosis involves patients, relatives and mental health personnel recognizing the early signs of psychosis. Twelve participants with psychotic illnesses narrated how they experienced becoming psychotic before they were admitted to acute psychiatric wards. The results of this study demonstrate that participants and their close others who sensed, understood and articulated experienced changes as signs of psychosis established a dialogue with mental health personnel and initiated treatment and care. Participants who did not perceive the experienced changes as signs of psychosis articulated the experienced changes as an awareness of a poor health condition and illness. These participants, who had no other people to advocate for them, appeared to experience poor communication and coercion during intervention. ABSTRACT: To assist in improving early interventions for psychosis, this study explored how adult people narrated their experience of becoming psychotic, and how contact with mental health personnel was established. Narrative interviews were conducted with 12 participants with psychotic illnesses recruited from acute psychiatric wards. The interviews were content analysed. Participants described being in a process of transition to psychosis as follows: experiencing changes as well-known signs of psychosis, experiencing sudden unexpected changes as signs of psychosis and experiencing unidentified changes as signs of illness. Our results show that participants and their close others who knew the signs of psychosis established a dialogue with mental health personnel and were better equipped to prevent and mitigate the psychosis. Our results demonstrate that participants who did not perceive the signs of psychosis and did not have other people to advocate for them were at risk for delayed treatment, poor communication and coercive interventions. Furthermore, participants who did not know the signs of psychosis perceived these changes as deterioration in their health and awareness of illness. We suggest that participants' experiential knowledge of transitioning to psychosis and an awareness of illness can be used to improve the communication during interventions for psychosis.